A fixed-point based distributed method for energy flow calculation in multi-energy systems - Zhang, Gang; Zhang, Feng; Meng, Ke; Zhang, Xin; Dong, Zhaoyang (IEEE, 2020)
Multi-energy flow calculation (M-EFC) is an essential tool for the coordinated analysis of strongly coupled electricity-gas-heating systems. However, the separate management of these subsystems poses a considerable challenge for designing a fast and reliable M-EFC method. In this paper, a fixed-point based distributed method is proposed for the M-EFC problem. The proposed method can preserve the autonomy of subsystems due to limited information exchange during the solution process. Moreo-ver, the fast and reliable convergence is achieved according to the proposed sufficient conditions based on the fixed-point theory. Besides, the proposed method is availa-ble for multi-energy systems (MES) with various coupling relationships and different structures of information ex-change. Simulations on a MES demonstrate that the pro-posed method has remarkable superiority compared to the unified Newton-Raphson method in computation time, accuracy and robustness against data loss.
Keywords: Distributed method; energy flow calculation; fixed-point; high-order nonlinear equation; multi-energy system